"On water" cascade synthesis of benzopyranopyrazoles and their macrocycles. Issue 15 (11th April 2018) - Muthusamy, Sengodagounder; Gangadurai, Chinnakuzhanthai
Graphical abstract: Highlights: Green approach to synthesize benzopyranopyrazoles in excellent yields. Water mediated intramolecular 1, 3-dipolar cycloaddition reaction. Cascade reaction under open to air atmosphere. Synthesis of pyrazole incorporated macrocycles. No catalyst as well as column purification. Abstract: Reported herein is an intramolecular 1, 3-dipolar cycloaddition strategy for rapid entry into benzopyranopyrazoles (BPP) on water medium as "open flask chemistry" approach. The in situ generation of diazo functionality in two-step sequence from the appropriate alkylated salicylaldehydes undergoes smooth [3 + 2]-cycloaddition with unactivated alkynes/alkenes furnishing benzopyranopyrazoles in good yield. This methodology was also extended for the synthesis of pyrazole incorporated macrocycles. This cascade protocol involving water medium provides an atom-economical and environment friendly approach.